A Sandpit for Systems Engineering and Systems Integration education and research. (28th December 2009) - Do, Quoc; Cook, Stephen C.; Campbell, Peter; Shoval, Shraga; Russell, Stephen; Mansell, Todd; Relf, Phillip
This paper describes the Microcosm programme established by the Defence Science and Technology Organisation and University of South Australia that seeks to provide a facility to explore systems integration issues, accelerate the formation of systems engineering competencies, and conduct research into model-based systems engineering. Firstly, the paper outlines the design drivers and long term goals of the programme. This is followed by a description of the Stage One implementation that covers the high-level architecture, system design, and implementation. The utility of the Microcosm Sandpit has been successfully demonstrated through a real-time intruder detection and engagement scenario using real and simulated autonomous robot vehicles.